PERBEDAAN ASUPAN ZAT GIZI ENERGI, PROTEIN, AKTIVITAS DAN STATUS GIZI MAHASISWA YANG TINGGAL DI ASRAMA DAN YANG TINGGAL DI LUAR ASRAMA POLTEKKES KEMENKES PONTIANAK - Oliver Dwiandra Arijuato; Didik Hariyadi; Desi (Media Gizi Khatulistiwa, 2025)
Background: A person's nutritional condition can reflect his/her health status and the effects of diet as seen from his/her body weight. Good nutritional status in students can support their academic performance (Alkaririn et al., 2022). The nutritional status of adolescents is influenced by various factors, including diet and physical activity. Based on Sarwa & Apriani's (2014) research, out of 96 samples studied, it was found that students' nutritional status was better when they lived in a dormitory than before, and according to Susmiati (2020), adolescents with low activity tend to have obese nutritional status. Objective: This study aims to determine the differences in nutritional status, energy and protein intake, and activity of students who live in dormitories and those who live outside the Pontianak Poltekkes Kemenkes dormitory. Methodology: Using quantitative analytical observational method and cross sectional design. The sample size was 150 students with details of 75 people living in the dormitory and 75 people living outside the dormitory. Results: Based on the results of the Independent T-Test test, the P value for differences in nutritional status (0.058), energy intake (0.055), protein intake (0.415) and physical activity (0.00). Conclusion: The study showed that there were no differences in energy intake, protein and nutritional status. However, there is a significant difference in the activity of students who live in the dormitory and those who live outside the dormitory.